1988
DOI: 10.1111/j.1471-4159.1988.tb01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Elements in Rat Peripheral Axons and Nerve Cell Bodies Determined by X‐Ray Microprobe Analysis

Abstract: X-ray microprobe analysis was used to determine concentrations (millimoles of element per kilogram dry weight) of Na, P, Cl, K, and Ca in cellular compartments of frozen, unfixed sections of rat sciatic and tibial nerves and dorsal root ganglion (DRG). Five compartments were examined in peripheral nerve (axoplasm, mitochondria, myelin, extraaxonal space, and Schwann cell cytoplasm), and four were analyzed in DRG nerve cell bodies (cytoplasm, mitochondria, nucleus, and nucleolus). Each morphological compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
6
30
0
Order By: Relevance
“…The morphological characteristics of myelinated axons and Schwann cells in cryosections of rat peripheral nerve have been well documented in previous studies (LoPachin et al, 1988;1990;1992a,h). In the present study, no significant changes in axon or glial cell morphology were observed in cryosections from rats of either diabetic or ganglioside treatment groups.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…The morphological characteristics of myelinated axons and Schwann cells in cryosections of rat peripheral nerve have been well documented in previous studies (LoPachin et al, 1988;1990;1992a,h). In the present study, no significant changes in axon or glial cell morphology were observed in cryosections from rats of either diabetic or ganglioside treatment groups.…”
Section: Resultssupporting
confidence: 58%
“…Morphological criteria used to identify analytical compartments in frozen sections were confirmed in a previous parallel study of conventionally fixed control rat peripheral nerve (LoPachin et a]., 1988). Given the relative paucity of nodes of Ranvier in peripheral nerves, the majority of our axonal measurements in transverse cryosections were probably of internodal axoplasm.…”
Section: Cryomicrotomy and Epmamentioning
confidence: 57%
See 3 more Smart Citations